2005
DOI: 10.1016/j.cellbi.2005.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Cellular organisation in meiotic and early post-meiotic rice anthers

Abstract: We have used fluorescent, confocal laser and transmission electron microscopy (TEM) to examine cellular organisations, including callose (1,3-beta-glucan) behaviour, in meiotic and early post-meiotic rice anthers. These features are critical for pollen formation and provide information to better understand pollen sterility caused by abiotic stress in rice and other monocotyledonous species. Among organelles during meiosis, abundant plastids, mitochondria and nuclei of the anther cells show distinctive features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 39 publications
3
67
0
Order By: Relevance
“…In plant vegetative organs, such as stems and leaves, it is believed that cuticular lipid biosynthesis occurs exclusively within epidermal cells (Sieber et al, 2000;Nawrath, 2002;Panikashvili et al, 2007). Previous reports showed that plastids could not been found in anther epidermal cells (Mamun et al, 2005a(Mamun et al, , 2005b, which implies that lipid de novo synthesis cannot occur within anther epidermal cells. Therefore, it is not surprising that several tapetum-expressed lipid metabolism genes are involved in anther cuticle formation (Li et al, 2010;Shi et al, 2011;Yang et al, 2014).…”
Section: Anther Cuticle and Pollen Exine Share One Common Aliphatic Smentioning
confidence: 92%
“…In plant vegetative organs, such as stems and leaves, it is believed that cuticular lipid biosynthesis occurs exclusively within epidermal cells (Sieber et al, 2000;Nawrath, 2002;Panikashvili et al, 2007). Previous reports showed that plastids could not been found in anther epidermal cells (Mamun et al, 2005a(Mamun et al, , 2005b, which implies that lipid de novo synthesis cannot occur within anther epidermal cells. Therefore, it is not surprising that several tapetum-expressed lipid metabolism genes are involved in anther cuticle formation (Li et al, 2010;Shi et al, 2011;Yang et al, 2014).…”
Section: Anther Cuticle and Pollen Exine Share One Common Aliphatic Smentioning
confidence: 92%
“…Acidocalcisome-like organelles have been reported in other plant organs with active cell division, such as in anthers during the onset of meiosis (Mamun et al 2005) and in meristematic areas of roots from pea and barley seedlings (Olbrich et al 2007). Interestingly, the vacuoles of these seedlings later merge together to form a central vacuole, similar to the merging of the acidocalcisomes and contractile vacuole of protists (Olbrich et al 2007).…”
Section: Polyp In Vascular Plants: Insights Into Embryo Developmentmentioning
confidence: 99%
“…At the premeiotic development stage, the epidermal cells have a well‐structured cuticle and contain a complete set of normal organelles. These cells during early meiotic development possess plastids containing amylaceous starch reserves (Mamun et al, 2005a). Sucrose exported from the adjacent endothecium (or due to sugars loading via anther wall cells from the filament) is stored as starch in these organelles (Mamun et al, 2005b).…”
Section: Cellular Organization Of Microsporogenesismentioning
confidence: 99%